Learning by doing – Farmers' specialized cooperatives development in China - Tursinbek Sultan; Karin Larsén; Zuhui Huang (Proceedings in System Dynamics and Innovation in Food Networks 2011, 2011)
In many of the developing (transition) countries, government is promoting the use of cooperatives as organizations that can help enhance the development of farmers and other communities. Agricultural cooperatives are believed to function as a tool for the government in promoting the economic and social development, in particular by creating employment, generating income, eradicating poverty and strengthen farmers' (market) power within the modern value chain. As for most transitional countries, Chinese government played a primary important role in agricultural cooperatives development. The government attempted to restructure the agro-food system to a modernized and industrialized one by supporting farmer cooperatives and producer organizations....
Keywords: 330